علاقة طريقة الحراثة برطوبة التربة وإنتاجية المحاصيل الحقلية* (Latakia University Journal -Biological Sciences Series, 2019)
تعتبر رطوبة التربة عاملاً محدداً لإنبات المحاصيل الحقلية ونموها وكذلك لإنتاجها وخاصة في المناطق ذات الهطول المنخفض وفي حالة الزراعة البعلية، لذلك فإن كل مامن شأنه أن يحافظ على رطوبة التربة ويحسن من كفاءة استخدامها يعتبر أمراً في غاية الأهمية, خاصة وأن التغيرات المناخية للكرة الأرضية حالياً تتجه نحو الجفاف, ومن هنا ظهرت مدارس جديدة لتهيئة التربة منها نظام الحراثة المخفضة  Minimum Tillage   ونظام الحراثة الصفريةZero-Tillage أو نظام اللاحراثة No-Tillage أو ما يسمى حاليا الزراعة الحافظة Conservation Tillage. والهدف الأساسي من استخدام هذه النظم المحافظة على التربة الزراعية من التعرية والانجراف وأيضاً التقليل من فقد ماء التربة وكفاءة استخدامها, وقد أثبتت الدراسات والأبحاث بان لنظام الحراثة تأثير ملحوظ على المخزون الرطوبي للتربة في موعد زراعة المحاصيل وخاصة في الأعوام الجافة, وأظهرت أن استخدام نظم الحراثة الصفرية أو الحراثة المخفضة يحافظ على رطوبة التربة مقارنة بالطريقة التقليدية للحراثة, حيث بلغ الفارق بالمدخر الرطوبي (بالمتوسط) في الطبقة الزراعية 0-30سم حوالي 5-10مم وهذا أثّر على نسبة الإنبات والنمو لاحقاً. كما زادت كفاءة المياه في نظم الحراثة المخفضة حيث بلغ الاستهلاك المائي لإنتاج وحدة الإنتاج من القمح حوالي 966.1م3/طن حبوب في الحراثة التقليدية /حقول الذرة/ مقابل 896.7 م3/طن حبوب. كما زادت إنتاجية المحصول بالمتوسط لعدة سنوات بمقدار تراوح من 150-180 كغ/هـ في حقول القمح بعد البرسيم و وصل إلى 280 كغ/هـ,  وفي حقول القمح بعد الذرة وبالمتوسط لـ 9سنوات في إحدى التجارب بلغ الفارق 530 كغ/هـ. Soil moisture is considered a determining factor for germination and growth of field crops and thus for production, especially in areas with low precipitation, and in the case of rain fed agriculture. Therefore, all measures which would preserve the soil moisture and improve utilization efficiency are considered extremely important, especially that because of climate change, the Earth is currently moving towards drought. Hence, new approaches to prepare the soil have been introduced, such as Minimum Tillage System, Zero-Tillage system, and No-Tillage or what is now called the Conservation Tillage. The main objective of using these systems is to maintain the agricultural soil from erosion and runoff and also to reduce the loss of soil water and utilization of its efficiency. Research and studies have shown that the plowing system has a significant impact on the stock of soil moisture at the time of crop cultivation, especially in dry years. They also show that the use of Zero-Tillage, or, Minimum Tillage Systems preserves soil moisture compared to the traditional method of plowing, as the variance of saver moisture was on average in the 0-30 cm layer about 5-10 mm, and this affected the rate of germination and growth later. Moreover, the efficiency of water in the minimum tillage systems has increased where the total water consumption for production of wheat production unit was about 966.1 m 3 / ton grain in the conventional tillage / maize fields / against 896.7 m 3 / ton grain. The average crop yield for several years has also increased by the range of 150-180 kg / ha in the fields of wheat after clover, and reached  280 kg / ha, and in wheat fields after corn, and the average for 9 years in one of the experiments the difference was 530 kg / ha.